Zaburzenia depresyjne wśród studentek i studentów w Polsce - Karmolińska-Jagodzik, Ewa (Studia Edukacyjne, 2019)
This article describes depressive disorders among contemporary students in Poland. The research results analyses data obtained in the national survey in 2019 on a group of 4,500 full-time and extramural students2. The selection of the research sample was consistent with a random selection. The research was carried out in a research team (Prof. dr hab. A. Cybal – Michalska, Prof. UAM, dr hab. S. Jaskulska, Prof. UAM, dr hab. N. Walter, Dr. M. Marciniak, Dr. E. Karmolińska – Jagodzik) under the guidance of prof. UAM, dr hab. Jacek Pyżalski under the grant implemented for the State Agency for Solving Alcohol Problems. Issues related to depression were within the scope of my analysis. This article includes a description of the causes of depression and the theoretical disorder itself. In addition, it article provides an analysis of the test results using the Beck test in individual subscales for students in Poland. The article is a diagnostic approach to the student community in Poland in the scope of the phenomenon discussed.